2013
DOI: 10.1091/mbc.e12-06-0488
|View full text |Cite
|
Sign up to set email alerts
|

Intermediate filament-associated cytolinker plectin 1c destabilizes microtubules in keratinocytes

Abstract: Plectin 1c (P1c), an intermediate filament-associated cytolinker protein, antagonizes the microtubule (MT)-stabilizing function of MT-associated proteins. Lack of P1c in keratinocytes leads to the stabilization of MTs and alters basic cellular features and functions, including cell shape, polarized migration, metabolism, and mitotic spindle formation.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

4
58
0
1

Year Published

2013
2013
2021
2021

Publication Types

Select...
7
2

Relationship

6
3

Authors

Journals

citations
Cited by 41 publications
(63 citation statements)
references
References 75 publications
4
58
0
1
Order By: Relevance
“…Co-sedimentation assays were adapted from Valencia et al (76). Samples of 5 M porcine brain tubulin in 30 l of tubulin buffer (80 mM PIPES, pH 6.9, 2 mM MgCl 2 , and 0.5 mM EGTA) were polymerized by the addition of 2 M MAP2c and incubated for 15 min at 37°C.…”
Section: Microtubular Co-sedimentation Assaymentioning
confidence: 99%
“…Co-sedimentation assays were adapted from Valencia et al (76). Samples of 5 M porcine brain tubulin in 30 l of tubulin buffer (80 mM PIPES, pH 6.9, 2 mM MgCl 2 , and 0.5 mM EGTA) were polymerized by the addition of 2 M MAP2c and incubated for 15 min at 37°C.…”
Section: Microtubular Co-sedimentation Assaymentioning
confidence: 99%
“…However, despite expectations that may have been raised by these studies, it has never been shown that plectinmediated interactions of IFs contribute to the stability of MT networks; neither has convincing evidence been reported that such interactions are instrumental in aligning or guiding MTs and IFs along each other, a function likely provided by other proteins, such as the tumor suppressor APC [60 ]. On the contrary, plectin deficiency, specifically of isoform P1c, leads to increased formation and stability of MTs in keratinocytes, myofibers, neurons, and (tendentiously) fibroblasts ( [51,61 ], and unpublished data). These observations are consistent with the idea that consolidation of IF structures through plectin favors the dynamic state of MTs and thus counteracts their stabilization, similar to the situation with actin filaments.…”
Section: If-networking Fosters Mt Dynamicsmentioning
confidence: 92%
“…Reported binding partners include actin, integrin-b4, nesprin, dystrophin, utrophin, vimentin, calmodulin, and PIP 2 , with more to expect. The SH3 domain of plectin mediates destabilization of MTs [61 ]. With a visualized length of 200 nm, plectin has the longest rod domain of all plakins.…”
Section: Hemidesmosomes and The Role Of P1amentioning
confidence: 99%
“…Finally, it should be noticed that plec1-1 and plec1-2 siRNAs treatments, after 72 h, triggered diminished growth rate of cells (20 -30% decrease of cell number in comparison with control siRNA due to cell death linked to aberrant mitosis; this has been reported for another plectin isoform (48)). …”
Section: Methodsmentioning
confidence: 60%